Exploring relationship between indistinguishability-based and unpredictability-based RFID privacy models - YANG, Anjia (Institutional Knowledge at Singapore Management University, 2018)
A comprehensive privacy model plays a vital role in the design of privacy-preserving RFID authentication protocols. Among various existing RFID privacy models, indistinguishability-based (ind-privacy) and unpredictability-based (unp-privacy) privacy models are the two main categories. Unp*-privacy, a variant of unp-privacy has been claimed to be stronger than ind-privacy. In this paper, we focus on studying RFID privacy models and have three-fold contributions. We start with revisiting unp*-privacy model and figure out a limitation of it by giving a new practical traceability attack which can be proved secure under unp*-privacy model. To capture this kind of attack, we improve unp*-privacy model to a stronger one denoted as unp(tau)-privacy. Moreover, we prove that our proposed privacy model is stronger than ind-privacy model. Then, we explore the relationship between unp*-privacy and ind-privacy, and demonstrate that they are actually not comparable, which is in contrast to the previous belief. Next, we present a new RFID mutual authentication protocol and prove that it is secure under unp(tau)-privacy model. Finally, we construct a RFID mutual authentication model denoted as MA model, and show that unp(tau)-privacy implies MA, which gives a reference to design a privacy-preserving RFID mutual authentication protocol. That is, if we propose a scheme that satisfies unp(tau)-privacy, then it also supports mutual authentication. (C) 2018 Elsevier B.V. All rights reserved.